2020
DOI: 10.1111/jcmm.16157
|View full text |Cite
|
Sign up to set email alerts
|

Complement C5 activation promotes type 2 diabetic kidney disease via activating STAT3 pathway and disrupting the gut‐kidney axis

Abstract: Type 2 diabetes mellitus (T2DM) is a severe disease characterized by elevated glucose levels due to insulin resistance or inadequate insulin secretion. Diabetic kidney disease (DKD) is one of the most severe microvascular complications of diabetes mellitus (DM) and is the leading cause of end-stage renal disease (ESRD) and renal failure. 1 DKD develops in approximately 35% of patients with T2DM 2 and is strongly

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 60 publications
1
33
0
Order By: Relevance
“…The upregulation of the complement system plays an important role in the development of T1DM and T2DM, as well as in the pathogenesis of the complications of DM [60]. It was documented that the complement system plays a significant role in the development of diabetic kidney disease [61][62][63], retinopathy [64], and periodontal destruction in patients with DM [65]. Interestingly, the mechanism by which the complement system promotes the development of diabetic kidney disease is the activating of the signal transducer and activator of transcription 3 (STAT3) pathway [63].…”
Section: Complement Systemmentioning
confidence: 99%
“…The upregulation of the complement system plays an important role in the development of T1DM and T2DM, as well as in the pathogenesis of the complications of DM [60]. It was documented that the complement system plays a significant role in the development of diabetic kidney disease [61][62][63], retinopathy [64], and periodontal destruction in patients with DM [65]. Interestingly, the mechanism by which the complement system promotes the development of diabetic kidney disease is the activating of the signal transducer and activator of transcription 3 (STAT3) pathway [63].…”
Section: Complement Systemmentioning
confidence: 99%
“…C5 can promote DKD by activating the STAT3 pathway and inducing inflammation in the kidneys, but SCFAs can partially offset its injurious effects. 53 A gut microbiome‐immune axis exists in the human body. Gut microbiota‐derived metabolites can pass through the intestinal epithelium and accumulate in the circulatory system.…”
Section: Mechanisms Behind the Effects Of Gut Microbiota On Dkdmentioning
confidence: 99%
“…miRNA-hub gene regulatory network and TF-hub gene regulatory network can be regarded as key to the understanding COVID-19 infection and its associated complications and might also lead to new therapeutic approaches. hsa-mir-4484 [552], hsa-mir-4511 [553], STAT3 [554], KLF5 [555], SRF (Serum response factor) [556], GATA3 [557] and USF1 [558] [574] and USF1 [575] have been shown to be activated in cardiovascular diseases. hsa-mir-3615 [576], hsamir-1825 [577], STAT3 [578], KLF5 [579], SREBF2 [580], GATA3 [Huda et al 2018] and USF1 [Meex et al 2008] were identified to be closely associated in patients with diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%
“…miRNA-hub gene regulatory network and TF-hub gene regulatory network can be regarded as key to the understanding COVID-19 infection and its associated complications and might also lead to new therapeutic approaches. hsa-mir-4484 [552], hsa-mir-4511 [553], STAT3 [554], KLF5 [555], SRF (Serum response factor) [556], GATA3 [557] and USF1 [558] have been implicated as a principal mediator of kidney diseases. Studies have reported that hsa-mir-190b [559], hsamir-4693-5p [560], hsa-mir-1470 [560], hsa-mir-1825 [561], STAT3 [562], SREBF2 [563] and SRF (Serum response factor) [564] are necessary for neurological diseases.…”
Section: Discussionmentioning
confidence: 99%